Pengaruh Verbal Abuse Orang Tua terhadap Perilaku Agresif Remaja Awal yang Bersekolah di Kecamatan Ujung Tanah Kota Makassar - Ningrum, Nurul Ayu Setya; Muh. Daud; Wilda Ansar (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
Aggressive behavior is both verbal and nonverbal behavior that is intentionally carried out to injure or harm others. Factors that influence the emergence of aggressive behavior in adolescents are the family environment and parents as a bad examples for adolescents. Aggressive behavior is caused by family factors where adolescents imitate these aggressive actions when parents provide exposure to verbal and nonverbal violence to adolescents. This study aims to determine the effect of parental verbal abuse on the aggressive behavior of early adolescents attending school in Ujung Tanah sub-district, Makassar City. The research method used is the quantitative method. The sample in this study amounted to 350 people who were early adolescents attending school in Ujung Tanah sub-district with an age range of 10–14 years and living with parents. Data analysis was performed using simple linear regression analysis with the help of IBM SPSS 24.0. The results showed a r-square value of 0.207 and a Sig. value of 0.000 (p < 0.05) which means that there is a significant influence of parental verbal abuse on the aggressive behavior of adolescents attending school in Ujung Tanah sub-district. The implication of this research is that preventive efforts need to be made in the form of providing education related to the impact arising from verbal abuse given by parents to adolescents. Providing this education is expected to minimize the emergence of aggressive behavior in early adolescents.